Efeitos socioespaciais do agronegócio canavieiro no sul goiano - Neves, Pedro Dias Mangolini (2019)
Since the 21st century, the southern region of Goiás has become one of the areas with the greatest expansion of cultivated area and sugarcane production with a strategic modification of the sugarcane capital under the consent of the State, through public policies to promote it, such as the National Alcohol Program – Proálcool, Strategic Plan for the Development of the Center-West – PEDCO, Constitutional Fund of the Center-West – FCO, Industrial Development Program of Goiás – PRODUZIR. Three guiding hypotheses emerge to face this issue: the first is that national strategies for the expansion of capitalism in Brazil include, among other actions, the expropriation of land to expand the sugarcane industry, water exploitation, expropriation of sources of energy, and even the social subjects involved in the field for such purposes. Another hypothesis is that the sugarcane agribusiness produces an environmental discourse, which, in turn, is supported on actions and discourses of the State, declaring it to be sector that produces "clean energy" in a sustainable way, thus legitimizing the appropriation of land and water for this activity. The third hypothesis is that the expansion of sugarcane production has been reducing food production in the state of Goiás, justified by a discourse of increasing the income (Gross Domestic Product per capita) of the municipalities with sugarcane mills. Therefore, the general objective of this research was to understand the new forms of accumulation and reproduction of sugarcane agribusiness as well as its socio-spatial effects in Goiás, which started with the National Agroenergy Plan (2006/2011). The specific objectives were to understand the expansion of sugarcane agribusiness and the new mechanisms of accumulation using spoliation in sugarcane agribusiness in addition to its social and spatial effects aiming at investigating the changes in capital and labor relations in sugarcane agribusiness as well as identifying new possibilities to expand sugarcane agribusiness. We developed our study using on-site fieldwork involving interviews with workers from sugarcane mills, representatives of unions, peasants and local public officials responsible for the Environment Secretariat as well as the Quirinópolis Trade and Industry Secretariat. In order to understand the socio-spatial effects, we carried out data collection and analysis of pesticide intoxication data at the Toxicological Information Center – CIT at the Health Surveillance Superintendence – SUVISA in the state of Goiás, and the collection and analysis of water capitation grants at the State Secretariat of Environment, Water Resources, Infrastructure, Cities and Metropolitan Affairs –SECIMA. We also used information from the Ministry of Labor and Employment – MTE (Data of the Annual Social Information Report – RAIS), Ministry of Agriculture, Livestock and Supply – MAPA and the Brazilian Institute of Geography and Statistics – IBGE. The results show that the expansion of sugarcane agribusiness in the South Meso-region of Goiás was benefited in the context of two main factors: Asian soybean rust, which reached the region in the early 2000s considerably reducing the price of land, and the trade balance unfavorable to exports, such as soybeans. From the analysis of the National Plan of Agroenergy as a policy of expansion of the sugarcane agribusiness, the justification for such investments was noted aiming at the generation (cogeneration) of energy through agroenergy, such as sugarcane. The productive restructuring of sugarcane agribusiness capital in Brazil revealed a scenario of territorial expansion and capital accumulation, leading to a modification of the sector in Brazil, making the sugarcane plants installed in the most recent areas, such as South of Goiás, different from the main plants in São Paulo, both regarding the area and type of production. Since São Paulo was initially focused on sugar production, another point refers to the management of these plants, which had a restructuring in groups and joint ventures. It is notable that among other actions that degrade nature and cause socio-spatial effects on life in society, the new mechanisms of accumulation through spoliation of sugarcane agribusiness focused on the mercantilization of nature, generate contamination by pesticides, the appropriation and contamination of land and water with vinasse causing a decrease in food production. This is all justified or camouflaged by an environmental discourse of clean energy and sustainable cultivation. It can not be denied that the expansion of sugarcane agribusiness in Goiás (South Meso-region Goiano) brought economic growth to the municipalities where the mills were installed and the municipal tax collection such as the Tax on Circulation of Goods and Services – ICMS doubled and even quadrupled in some municipalities. There was also an increase in the number of services available in these municipalities, such as educational establishments, hotel chains and bars and restaurants. However, as a consequence, a portion of local producers (peasants, farmers and ranchers) had no other choice but to join the mills investors, becoming lessees or suppliers of sugarcane, reducing the production of diversified foods. We concluded that the new policy for the state of sugarcane agribusiness, the National Biofuels Policy – RenovaBio, has the main purpose of encouraging the generation of biofuels in Brazil justified by the agreement established at the Paris Conference. In addition, with the implementation of the RenovaBio, the production of agrofuels (including ethanol) in Brazil tends to increase and will evidently lead to an increase in the productivity of sugarcane agribusiness through improved technology in the mechanization and genetics of sugarcane variety, which may intensify the expansion of sugarcane areas to the Southwest Meso-region of the state of Goiás in the remaining areas of Cerrado.